1992
DOI: 10.1002/jcb.240490404
|View full text |Cite
|
Sign up to set email alerts
|

The phosphatidylinositol transfer protein in 3T3 mouse fibroblast cells is associated with the Golgi system

Abstract: By use of indirect immunofluorescence it was shown that the phosphatidylinositol transfer protein (PI-TP) in 3T3 mouse fibroblast cells is associated with the Golgi system. This was concluded from double-labeling experiments with TRITC-labeled Ricin which binds to sugar residues that are specifically processed in the Golgi system. Independent evidence for this association was provided by the fact that dissociation of the Golgi system by brefeldin A was reflected in an extensive redistribution of PI-TP labeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Total cell lysates were obtained by lysis of the cells in 50 mM Hepes, pH 7.4, 150 mM NaCl, 5 mM EDTA, 0.5% NP-40, 0.5% sodium deoxycholate, 0.1% sodium dodecyl sulfate (SDS), 5 g/ml leupeptin, 10 mM NaF. Subsequently, proteins were separated by SDS-polyacrylamide gel electrophoresis in 12% acrylamide and 0.37% bis-acrylamide [12] and transferred to a nitrocellulose membrane (Schleicher & Schuell BA 85) by semidry Western blotting in a Multiphor II Nova Blot electrophoretic transfer unit (Pharmacia, Uppsala, Sweden) at 1 mA/cm 2 for 1 h at room temperature. The nonspecific binding sites of the nitrocellulose membrane were blocked by incubating the membrane for 1 h in 2% nonfat dry milk (w/v) in 20 mM Tris-HCl, pH 7.5, 0.5 M NaCl (TBS) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Total cell lysates were obtained by lysis of the cells in 50 mM Hepes, pH 7.4, 150 mM NaCl, 5 mM EDTA, 0.5% NP-40, 0.5% sodium deoxycholate, 0.1% sodium dodecyl sulfate (SDS), 5 g/ml leupeptin, 10 mM NaF. Subsequently, proteins were separated by SDS-polyacrylamide gel electrophoresis in 12% acrylamide and 0.37% bis-acrylamide [12] and transferred to a nitrocellulose membrane (Schleicher & Schuell BA 85) by semidry Western blotting in a Multiphor II Nova Blot electrophoretic transfer unit (Pharmacia, Uppsala, Sweden) at 1 mA/cm 2 for 1 h at room temperature. The nonspecific binding sites of the nitrocellulose membrane were blocked by incubating the membrane for 1 h in 2% nonfat dry milk (w/v) in 20 mM Tris-HCl, pH 7.5, 0.5 M NaCl (TBS) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-PI-TP antibodies were raised in rabbits against synthetic peptides representing the amino acid sequence of predicted epitopes in rat brain PI-TP␣ (39). Geneticin G418 and goat anti-rabbit IgG conjugated with alkaline phosphatase were obtained from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…Localization studies by indirect immunofluorescence and by microinjection of fluorescently labeled purified PI-TP␣ and PI-TP␤ into intact mammalian cells have shown that PI-TP␣ is mainly localized in the nucleus and in cluster-like structures in the cytosol and that PI-TP␤ is mainly associated with the Golgi membranes (3,4,39,40). However, upon stimulation of the cells by different growth factors (bombesin, PDGF) that stimulate the phospholipase C-dependent degradation of PtdIns(4,5)P 2 , accumulation of PI-TP␣ near the plasma membrane was not observed.…”
Section: The Addition Of Pi-tp␣ To a Total Lysate Of Myo-[mentioning
confidence: 99%
See 2 more Smart Citations